Prediksi Pemenuhan Ruang Terbuka Hijau Publik Singkawang Kota Berbasis Demografi dan GIS - Fitrianingsih, Yulisa; Irsan, Robby; Rangga, Boy; Nurbudi, Muhammad Tegar; Ghaisani, Hilda Putri (Universitas Tanjungpura, 2026)
Singkawang City is one of the cities frequently visited by domestic tourists in West Kalimantan Province. The need for space for built-up land and urban infrastructure continues to increase along with population growth. This phenomenon will reduce urban vegetation area, thereby allowing urban emissions to continue to grow. For this reason, developing green open spaces as a bioengineering technique and creating relatively cheaper, healthier, safer, and more comfortable biofilters are necessary. The purpose of this study is to analyze the need for public green open spaces based on area and population using the overlay method, and to digitize the distribution map of existing green open spaces in Singkawang City. Based on the results and discussions in this study, it can be concluded that the area of public green open space needed in Singkawang City is 791.12 Ha, and the City still lacks 476.98 Ha of public green open space. Meanwhile, the need for public green open space per capita in West Singkawang District from 2025 to 2035 has been met by an existing public green open space area of 175.6 Ha. In Central Singkawang District, from 2025 to 2028, there was an existing public green open space of 159.69 Ha, but from 2029 to 2035, there was a shortage of public green open space of 15.09 Ha